2015
DOI: 10.3390/e17127854
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Image Tampering Detection Method Based on Maximum Entropy Criteria

Abstract: This paper proposes a novel image watermarking method based on local energy and maximum entropy aiming to improve the robustness. First, the image feature distribution is extracted by employing the local energy model and then it is transformed as a digital watermark by employing a Discrete Cosine Transform (DCT). An offset image is thus obtained according to the difference between the extracted digital watermarking and the feature distribution of the watermarked image. The entropy of the pixel value distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Also, Yang and Qiu [14] investigated the flow distribution by introducing entropy theory. Actually, the entropy measurement is a famous theory proposed by Abbas [15] and it has been broadly used in many fields, such as energy analysis [16], information clustering [17], accurately prediction [18], image watermarking [19] and mass density measurement [20]. However, it is found that there are only a few researches about military supply based on entropy theory, until Zhou et al [21] proposed a double-entropy model to address the issue of concealment measurement and detection.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Yang and Qiu [14] investigated the flow distribution by introducing entropy theory. Actually, the entropy measurement is a famous theory proposed by Abbas [15] and it has been broadly used in many fields, such as energy analysis [16], information clustering [17], accurately prediction [18], image watermarking [19] and mass density measurement [20]. However, it is found that there are only a few researches about military supply based on entropy theory, until Zhou et al [21] proposed a double-entropy model to address the issue of concealment measurement and detection.…”
Section: Introductionmentioning
confidence: 99%
“…The SLIHAP method proposed in this paper solves the above problems well and realizes the dynamic evaluation of the HVDC protection systems. To make the evaluation results consider the subjective ambiguity of experts and contain subjective and objective theory, we constructed a new weighting method based on the IAHP method and the maximum entropy criterion (MEC) [42]. Since the traditional linear weighting method can only simply combine the weighting results of the two weighting methods in a specific ratio, it is impossible to form a new evaluation method by introducing objective theory into the subjective evaluation method.…”
Section: The Sliahp Methodsmentioning
confidence: 99%
“…The MEC is a criterion for selecting the statistical characteristics of random variables that best meets the objective situation [42]. When the MEC is introduced into the evaluation field, random variables can be replaced with weights.…”
Section: B Mecmentioning
confidence: 99%
“…Zhao et al [29] introduce a tampering detection technique that employs maximum entropy criteria. The Itti model [30] is applied to the original image to generate a saliency map, which is utilized as the watermark.…”
Section: Introductionmentioning
confidence: 99%